Intoxicación crónica por mercurio: reacción de las mucosas orales - Tasama, Carlos; Arbeláez, Ana Lucía (Revista Estomatología, 1995)
The cronic and acumulatives effects of small dosis of mercury can produce moments of agudization of its toxicity and risks ofimportance en relation with human morbi-mortality. The socalledamalgan tatoesoftheoral mucosa are studied from the amatomopathological point of view.